Rapid resolution of reversible bronchiectasis after Mycoplasma pneumoniae pneumonia in an adult: A case report. Issue 13 (March 2019) - Guo, Qi; Li, Hai-yan
Abstract: Rationale: Bronchiectasis results when inflammatory and infectious damage to the bronchial and bronchiolar walls leads to a vicious cycle of airway injury. On the basis of the classic characteristic, that is, permanent bronchial dilatation, bronchiectasis is generally considered irreversible in the adult population. Patient concerns: A 21-year-old woman presented to our hospital with a 9-day history of productive cough and fever. Diagnosis: Bronchiectasis after Mycoplasma pneumoniae pneumonia. Interventions: The patient was treated with azithromycin for 7 days. Outcomes: The bronchial dilatation resolved as evidenced by sequential chest high-resolution computed tomography 7 days and 1 month later, respectively. Lessons: Although complete disappearance is quite rare in adult, this case demonstrated that bronchial dilatation might resolve completely in such a fascinating short period of time if receiving adequate and timely regimens.